Perceptions from municipal managers regarding the implementation of ageing-focused public policies in a reference municipality in Rio Grande do Sul Perceptions from healthcare professionals regarding the implementation of ageing-focused public policies in Canoas/RS - Rosa, Luiz Gustavo Fernandes da (2022)
The goal was to understand the municipal managers’ perceptions regarding the implementation of ageing-focused public policies in Canoas municipality. We conducted five interviews with municipal managers, which were then submitted to a Content Analysis, reaching these categories: Ageing according to managers; municipal public policies; and work strategy. Public policies are implemented, and the managers are engaged in the consolidation of support networks.